Artful dodgers reconceiving the golden age of children's literature - Gubar, Marah, 1973- (Oxford University Press, 2009)
In this account of the Golden Age of children's fiction, Gubar redefines the phenomenon known as the 'cult of the child'. She looks at the works of Lewis Carroll, Frances Hodgson Burnett and J. M. Barrie, contending that they reject the simplistic 'child of Nature' paradigm in favor of one based on the child as an artful collaborator.